Design and simulation of hyperspectral lens system for a flood monitoring CubeSat - Rosadi, Audrey; Pebrianti, Dwi; Bayuaji, Luhur; Riyanto, Indra (IEEE, 2026)
Flooding is one of the most severe environmental disasters, impacting millions of lives and causing significant economic losses. Effective flood monitoring is therefore essential to support timely disaster response, resource management, and damage assessment. However, current optical remote sensing methods to monitor floods, particularly multispectral imaging (MSI), are limited by low spectral resolution and rely heavily on complex post-processing algorithms to extract accurate flood information, leading to higher computational costs and reduced efficiency. To address this limitation, this study presents the hardware design and simulation of a high-resolution hyperspectral lens system optimized for CubeSat deployment. The optical system was modeled and optimized in ANSYS Zemax OpticStudio, targeting a spatial resolution of 30 meters with a 20-degree field of view across 24 spectral bands from 465–810 nm. The final design achieved an effective focal length of 133.394 mm and a total system length of 142.087 mm, with a compact weight of approximately 590 grams, making it suitable for 2U CubeSat integration. Performance analysis confirmed strong imaging quality, with an Airy disk radius of 7.937 micrometers and a Strehl ratio of 0.942. These results demonstrate the system’s capability to deliver high-resolution imaging with minimal reliance on post-processing, offering a compact and efficient optical solution for spaceborne flood monitoring.